Alveolar Ridge Preservation Using Leukocyte and Platelet-Rich Fibrin: A Report of a Case - Mogammad Thabit Peck; Johan Marnewick; Lawrence Stephen (Case Reports in Dentistry)
In order for a dental implant to be restored optimally, it must be placed in an ideal anatomic position. However, this is not always possible, since physiological wound healing after tooth removal, often results in hard and soft tissue changes which ultimately compromises ideal implant placement. With the aim of minimising the need for tissue augmentation, several alveolar ridge preservation (ARP) techniques have been developed. These often require the use of grafting material and therefore increase the risk of disease transmission. Leukocyte and platelet-rich fibrin (L-PRF) is a newly developed platelet concentrate that is prepared from the patient's own blood. Clinical research has indicated that it improves wound healing and stimulates bone formation. We present a case where L-PRF was successfully used in an ARP procedure to facilitate implant placement in a compromised extraction socket.